Symptoms among emerging adults with inflammatory bowel disease: a descriptive study. Issue 1 (10th October 2019) - Kamp, Kendra; Dudley‐Brown, Sharon; Heitkemper, Margaret; Wyatt, Gwen; Given, Barbara
Abstract: Individuals with inflammatory bowel disease (IBD) are commonly diagnosed when they are between the ages of 18–29, a developmental period known as emerging adulthood. Typically, emerging adults are subsumed into the category of adults even though emerging adults have unique developmental needs. In this descriptive study of IBD in emerging adults, the aims were to (a) determine the prevalence of symptoms; (b) describe the severity of symptoms and their interference with daily activities; and (c) examine the association between individual symptom severity and presence of fatigue. Emerging adults with IBD were recruited using web‐based convenience sampling. Sixty‐one individuals met the inclusion criteria. They had a mean age of 24.7 and a disease duration of 6.4 years. The most prevalent symptoms reported were: fatigue ( n  = 44, 72.1%), abdominal cramps ( n  = 39, 63.9%), abdominal pain ( n  = 39, 63.9%), and diarrhea ( n  = 38, 62.3%). The symptom with the greatest severity and interference with daily activities was fatigue. Abdominal cramps, abdominal pain, diarrhea, passing gas, and abdominal tenderness were associated with fatigue when controlling for age, emerging adulthood, gender, time since diagnosis, and current steroid use. Among emerging adults with IBD, fatigue is the most prevalent symptom and is the symptom with the greatest severity and interference with daily activities. These results suggest a need for interventions aimed at reducing both fatigue and gastrointestinal symptoms among emerging adults with IBD.